2018
DOI: 10.4103/ijnm.ijnm_158_17
|View full text |Cite|
|
Sign up to set email alerts
|

The Radioprotective Effects of Curcumin and Trehalose Against Genetic Damage Caused By I-131

Abstract: Background:Thyroid cancer has been growing rapidly during the last decades. Radioiodine-131 (I-131) as an appropriate therapy modality is currently using in the treatment of cancer and hyperthyroidism diseases. This radiotracer is considered as a cause of oxidative DNA damage in nontarget cells and tissues. The aim of this study was to investigate the effects of curcumin and trehalose on the level of DNA double-strand breaks (DSBs) caused by I-131 in human lymphocytes.Materials and Methods:First, 6-mL blood sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“… 4 , 5 , 6 , 7 Recent studies have identified a new type of ncRNA, termed circular RNA (circRNA). 8 , 9 , 10 Many circRNAs have been shown to be produced from the exons of coding genes, and several of them do not translate to proteins. 8 , 10 , 11 Figure 1 summarizes the biogenesis of various ncRNAs, including miRNAs, 5 , 12 , 13 siRNAs, lncRNAs, 4 and circRNAs.…”
Section: Introductionmentioning
confidence: 99%
“… 4 , 5 , 6 , 7 Recent studies have identified a new type of ncRNA, termed circular RNA (circRNA). 8 , 9 , 10 Many circRNAs have been shown to be produced from the exons of coding genes, and several of them do not translate to proteins. 8 , 10 , 11 Figure 1 summarizes the biogenesis of various ncRNAs, including miRNAs, 5 , 12 , 13 siRNAs, lncRNAs, 4 and circRNAs.…”
Section: Introductionmentioning
confidence: 99%
“…Radioprotector agents can be used to prevent or reduce DNA DSBs in peripheral lymphocytes induced by radiation. [ 18 19 20 21 22 ] For instance, it has reported that melatonin can enhance DNA repair induced by ionizing radiation, chemotherapeutic drugs, and some other mutagens which this property of melatonin is directly related to its interaction with enzymes involved in DNA repair. [ 23 24 25 26 ] In this regard, for example, this radioprotector through direct phosphorylation of Ser15 in p53 inhibits cell proliferation, providing more time for repairing the damaged DNA; hence, the accumulated DNA damage is avoided as well as cell death or probability of genomic instability is reduced.…”
Section: Introductionmentioning
confidence: 99%
“…In the article titled “The Radioprotective Effects of Curcumin and Trehalose Against Genetic Damage Caused By I-131”, published on pages 99-104, Issue 2, Volume 33 of Indian Journal of Nuclear Medicine[ 1 ], the name of the sixth author is written incorrectly as “Bagher Fahood” instead of “Bagher Farhood”.…”
mentioning
confidence: 99%